Pan-colonic pressurizations associated with relaxation of the anal sphincter in health and disease: a new colonic motor pattern identified using high-resolution manometry - Corsetti, Maura; Pagliaro, Giuseppe; Demedts, Ingrid; Deloose, Eveline; Gevers, Annemie; Scheerens, Charlotte; Rommel, Nathalie; Tack, Jan (Nature Publishing Group, 2017)
Background: Only few studies have applied high-resolution manometry (HRM) to the study of colonic motility in adults and none of them have concurrently evaluated colonic and anal motor activity. Aims: To evaluate colonic and anal motor activity by means of HRM in healthy subjects. As the present study revealed the presence of a new colonic motor pattern (pan-colonic pressurizations) in healthy subjects, three additional studies were conducted: the first and the second to exclude that this motor event results from an artefact due to abdominal wall contraction and to confirm its modulation by cholinergic stimulation and the third, as pilot study, to test the hypothesis that this colonic pattern is defective in patients with chronic constipation refractory to current pharmacological treatments. Methods: In both volunteers and patients the HRM catheter was advanced proximally during colonoscopy. Results: In all subjects, pressure increases of 15±3 mmHg and 24±4s simultaneously occurring in all colonic sensors (pan-colonic pressurizations), associated with anal sphincter relaxation were identified. Subjects had 85±38 pan-colonic pressurizations which increased significantly during meal (p=0.007) and decreased afterward (p=0.01), and were correlated with feelings of and desire to evacuate gas. The mean number of propagating sequences was 47±39, and only retrograde increased significantly postprandially (p=0.01). Pan-colonic pressurizations differed from strain artifacts and significantly increased after prostigmine. In patients pan-colonic pressurizations were significantly reduced as compared to volunteers. Conclusions: Pan-colonic pressurizations associated with relaxations of the anal sphincter represent a new colonic motor pattern which seems to be defective in patients with treatment-refractory chronic constipation and may play a role in the transport of colonic gas and in the facilitation of the propagating sequences-induced colonic transport.